OPEN INNOVATION AND THE COMPARISON BETWEEN STARTUPS AND INCUMBENT FIRMS IN SPAIN (Revista Galega de Economía)
This study compares the open innovation strategy between startups and incumbent firms over a period of ten years (2004-2013). Using a sample of startups and incumbent Spanish firms, we find that they differ considerably, and that this has implications for management. Incumbent firms and startups differ in terms of their use of external cooperation activities as a source of innovation. The lack of financial and human resources of startups leads them to open their borders more than incumbent firms, and startups benefit from being flexible, as they have yet to implement routines. This boosts startups’ innovation performance.